0240 Monitoring of asbestos fibre dispersion from a factory to surrounding residential environment. (21st August 2017) - Kang, Dongmug; Kim, Youngki; Kim, Jongeun; Choi, Hyunwoo
Abstract : Background: Although many studies on occupational or environmental exposure levels of asbestos have been published, it is hard to find studies that checked asbestos levels of both of inside and outside of asbestos factory. This fact make epidemiologists connect occupational and environmental asbestos exposure and health outcome simultaneously. One large asbestos textile factory, which was moved from Japan around year 1970, moved from Korea into Indonesia around year 1990. Methods: The study was conducted during 26-28th August 2008 in Cibinong, Indonesia. The field survey was carried out to check current workers' and environmental exposure level of the factory that was moved from Korea. The observed asbestos environmental asbestos levels were compared with atmospheric dispersion models (AERMOD). Results: Inside of the factory, the highest airborne asbestos concentration was 86 times higher than the permit level 0.1fiber/cc. The working condition was similar with 80 s' of Korean working condition. Dispersion pattern of asbestos from a factory was related with wind direction. The correlation coefficient (r) and determination coefficient (r 2 ) between air monitoring data and simulation data with AERMOD were 0.85 and 0.72 respectively. Conclusion: We confirm that asbestos workers in Indonesia had high exposure level of asbestos without proper protecting devices. Substantial level of environmental dispersion of asbestos from asbestos factory were found. This data can be used for basis of environmental exposure assessment for environmental asbestos related diseases. In addition, it is needed to transfer knowledge to protect hazards of asbestos with efforts to ban it to asbestos using countries.